Atezolizumab plus platinum-based chemotherapy as first-line therapy for metastatic urothelial cancer: A cost-effectiveness analysis - Xiaoyan Liu; Xiaoyan Liu; Yitian Lang; Qingqing Chai; Yan Lin; Yahui Liao; Yizhun Zhu (Frontiers Media S.A., 2022)
Purpose: According to the IMvigor130 trial, adding atezolizumab to platinum-based chemotherapy was effective in the treatment of metastatic urothelial cancer (mUC). Based on the perspective of the United States and China, the current study evaluated cost-effectiveness of atezolizumab plus chemotherapy for mUC patients in the first-line setting.Methods: A partitioned survival model was adopted for mUC patients. The survival data were derived from the IMvigor130 trial. Direct cost values were collected from the Centers for Medicare and Medicaid Services (CMS), Chinese Drug Bidding Database, and published literatures. The utility and toxicity data were gathered from related research studies and IMvigor130 trial. The incremental cost-utility ratios (ICURs) and incremental cost-effectiveness ratios (ICERs) were calculated and analyzed. Scenario analyses and sensitivity analyses were performed to observe the outputs and uncertainties.Results: The base-case analysis showed that the ICUR of atezolizumab plus chemotherapy versus chemotherapy in American and Chinese settings is $ 737,371 /QALY and $ 385,384 /QALY, respectively. One-way sensitivity analyses showed that the ICUR ranged from $ 555,372/QALY to $ 828,205/QALY for the United States. Also, the range was from $ 303,099/QALY to $ 433,849/QALY in the Chinese setting. A probabilistic sensitivity analysis showed the likelihood that atezolizumab plus chemotherapy becoming the preferred strategy was a little low even if the price reduction strategy was applied.Conclusion: Adding atezolizumab to chemotherapy improved survival time, but it is not a cost-saving option compared to chemotherapy for metastatic urothelial cancer patients in the American and Chinese settings.